Exploring the Insights: Unraveling the Knowledge, Attitude, and Practice of Diabetics Regarding Diabetes and Diabetic Retinopathy in Hail, Saudi Arabia - Alanezi, Njoud S; Alshammari , Layan K; Albahar , Fatima K; Alshammari, Shuruq O; Albahar , Maryam K; Alrashidi, Khalid M; Albedair, Abdulilah A; Syed, Abrar A; Syed, Bilal A; Saleem, Mohd; Syed Khaja, Azharuddin Sajid (Indian Journal of Community Health, 2024)
Background: Diabetes Mellitus is a metabolic disorder causing high blood glucose levels and is a major health concern in Saudi Arabia (SA). Aims & objectives: This study aimed to assess the knowledge, attitude, and practices of diabetic patients towards diabetes and diabetic retinopathy (DR) in Hail, SA. Methods: A descriptive cross-sectional survey using an anonymous, structured, validated, and pilot-tested questionnaire was conducted between February and June 2023 from adult diabetic patients in Hail and analyzed using RStudio. Associations between variables were evaluated, with statistical significance set at p < 0.05. Results: 280 participants took part in the survey, with 57.0% females and 51.4% aged between 18 to 34 years. Poor knowledge was significantly higher among participants aged 35 to 50 years (92.8%). Negative attitudes were more prevalent in males (37.8% vs 24.7%, p = 0.019) and those with lower income levels (16.7%, 29.5%, and 62.5% among high-, middle-, and low-income groups, respectively, p = 0.008). Conclusions: The study revealed a lack of knowledge and negative attitudes towards diabetes, particularly among lower-income patients. There is a significant relationship between education and good disease control, highlighting the need for improved education and awareness of DM and DR in Hail.